The Safety and Efficacy of the Modified Single Incision Non-thoracoscopic Nuss Procedure for Children With Pectus Excavatum - Song, Jishuo; Wang, Quan; Pan, Zhengxia; Wu, Chun; Li, Yonggang; Wang, Gang; Dai, Jiangtao; Xi, Linyun; Li, Hongbo (Frontiers in Pediatrics, 2022)
Background: This study described and evaluated the safety and efficacy of a modified single incision non-thoracoscopic Nuss procedure in pectus excavatum (PE) children. Methods: A retrospective study was performed that included patients with PE who underwent the non-thoracoscopic Nuss procedure at the Children’s Hospital of Chongqing Medical University between January 2017 and December 2020. The patients were divided into two groups according to the operation procedure: the double incision Nuss (DN) group and the modified single incision Nuss (SN) group. Propensity score matching (PSM) was applied before evaluation of operative and postoperative characteristics to reduce selection bias. Results: Of the 502 patients included, 261 were enrolled in the DN group, and 241 in the SN group. The operation time [35.0 (30.0-40.0) vs. 50.0 (40.0-55.0) minutes, P<0.001], blood loss [2.0 (1.0-5.0) vs. 5.0 (2.0-5.0) ml, P<0.001], and postoperative inpatient stay [7.0 (6.0-8.0) vs. 7.0 (7.0-8.0) days, P<0.001] of the patients in the SN group were all significantly less than those of the patients in the DN group after PSM. There were no significant differences in the incidence of complications between the two groups (P>0.05). Bar removal was performed in 85 patients in the SN group at 24-40 months postoperatively. Additionally, the Haller index (HI) after bar removal of the patients in the SN group was significantly lower than the initial HI [2.36 (2.15-2.55) vs. 3.76 (3.18-4.26), P < 0.001]. Conclusion: Our results show that the modified single incision non-thoracoscopic Nuss procedure for PE has great advantages in terms of a shorter duration of surgery and duration of postoperative stay, less blood loss, and excellent cosmetics. The modified procedure is safe and effective children with PE and is worthy of clinical application.